Parenting in the time of COVID-19: Insights and lessons from parents of international school children. (December 2022) - Doll, Kathleen; Calnin, Gerard; Ragan, Moira; Mason, Sarah; House, Kevin
The closure of school buildings due to COVID-19 and the resulting rapid transition to online education dramatically altered the lives of educators, students and parents. While previous literature demonstrates the vital role of parents in effective online education (Hattie, 2020; Liu et al, 2010), pre-pandemic literature focuses on parents and students who have opted in to online education. As such, the outbreak of COVID-19 has presented new challenges for understanding the relationship between parents and their child/ren's online learning. Since the start of the pandemic, studies have emerged exploring parental experience adjusting to their child/ren's online remote learning (Bhamani et al, 2020; Brom et al, 2020; Dong et al, 2020; Garbe et al, 2020; Lee et al, 2021). However, less is known about the online learning experiences during COVID-19 of families with children enrolled within international schools. Accordingly, the present study draws upon insights from 44 parents of children attending international schools who took part in 22 focus groups, across three countries and in three languages. The study investigates the parental experience with online education and unpacks four themes that emerged from the data: challenges faced by parents, parental perception of their child/ren's wellbeing, impressions of the learning quality and parental suggestions for consideration by school leadership. With these findings, school leaders have a unique opportunity to leverage lessons learned and support parental growth so that families, educators and students may all contribute to the promise of a brighter educational future.